A Comparative Study on Circumference of Selected Body Parts of 13 Years Old Boys of Four Different Altitudes of Darjeeling District - Gurung, Jyan Chandra (Journal of Sports Research, 2015)
The purpose of the study was to find out the difference in circumference of different Body parts of 13 years old boys of Darjeeling. The samples are school students. Researcher had taken 100 male students each from Sukhia Pokhari Higher Secondary School (Alt.-7200 ft.), Trunbull higher Secondary school (Alt.-6700 ft.), Jnanpith High school (Alt.-3000 ft.) and Kadamtala High School(Alt.-430 ft.). Researcher had measured height and weight as personal data measured circumference of head, neck, arm relax, flex arm, waist, gluteal, calf and ankle. It has been observed that there were significant differences in neck, wrist and calf circumference.